THE ROLE OF DIGITAL SKILLS IN THE GLOBAL LABOR MARKET: TRENDS AND IMPLICATIONS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
The global labor market is transforming due to technological advancements, making digital skills essential for employability and economic growth. As industries increasingly rely on automation, artificial intelligence (AI), and data-driven decision-making, workers must adapt to new technological demands to remain competitive.